The main aspects of the development of the airport security system - Nikishkin A. V., Stepanov I. V., Popovich O. A. (Scientific studies and modern education, 2018)
The article deals with the protection of airport complexes and adjacent territories as a multilateral and multi-stage system, ensuring the safety of life and health of passengers and the safety of things and goods.
Keywords: инфраструктура; infrastructure; авиационная безопасность; средства периметровой сигнализации; досмотрово-поисковая техника; Aviation security; perimeter alarm systems; inspection and search equipment